STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU LAYANAN PENDIDIKIAN - Rochmat Widodo; Fisman Bedi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The research describes the principal's leadership strategies in improving the quality of educational services. This research was conducted at the Baitul Insan Integrated Islamic Elementary School in Gedong Tataan District, Pesawaran Regency, Lampung Province. The research method uses a qualitative approach with a case study approach. Data collection techniques include interviews, observations, and documentation. From the research findings, it can be concluded that leadership strategies are implemented based on two perspectives, namely internal and external. In an internal perspective, which includes teachers and staff, the principal implements a democratic leadership strategy. Through democratic leadership, the principal optimizes the active participation of teachers and staff in decision-making, thereby creating a collaborative work environment focused on quality improvement. Meanwhile, from an external perspective, which includes the community, parents, and other stakeholders, the principal implements a leadership strategy oriented towards a humanistic approach. The humanistic approach emphasizes communication and community involvement, where the principal is responsive to the community's aspirations to build public trust and strengthen the school's positive image. The synergy of these two approaches enables the school to realize quality educational services through the integration of internal and external support.Keywords: Strategy, Leadership, Quality of Educational Services Abstrak: Penelitian mendeskripsikan strategi kepemimpinan Kepala Sekolah dalam meningkatkan mutu layanan pendidikan. Penelitian ini dilaksanakan di Sekolah Dasar Islam Terpadu Baitul Insan Kecamatan Gedong Tataan Kabupaten Pesawaran Provinsi Lampung. Metode penelitian menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi.Â  Dari hasil penelitian dapat disimpulkan bahwa strategi kepemimpinan diterapkan berdasarkan dua perspektif, yakni internal dan eksternal. Dalam perspektif internal, yang mencakup guru dan staf, kepala sekolah mengimplementasikan strategi kepemimpinan demokratis. Melalui kepemimpinan demokratis, kepala sekolah mengoptimalkan partisipasi aktif guru dan staf dalam pengambilan keputusan, sehingga tercipta iklim kerja yang kolaboratif dan berorientasi pada peningkatan mutu. Sementara itu, dari sudut pandang eksternal, yang mencakup masyarakat, wali murid dan stakeholder lainnya, kepala sekolah menerapkan strategi kepemimpinan yang berorientasi pada pendekatan humanis.Â  pendekatan humanis menitikberatkan pada komunikasi dan keterlibatan masyarakat, di mana kepala sekolah responsif terhadap aspirasi komunitas guna membangun kepercayaan publik serta memperkuat citra positif sekolah. Sinergi kedua pendekatan ini memungkinkan sekolah untuk mewujudkan layanan pendidikan yang berkualitas melalui keterpaduan dukungan internal dan eksternal.Kata kunci: Strategi, Kepemimpinan, Mutu Layanan Pendidikan